Evaluation of the Community Structure Leafminer Fly, Liriomyza spp. (Diptera: Agromyzidae) and Their Parasitoids on Various Host Plant Families in Bali Province - I Wayan Supartha; I Wayan Susila; Aunu Rauf; B. Merle Shepard; I Wayan Eka Karya Utama; I Wayan Sandikayasa; I Kadek Wisma Yudha; Putu Angga Wiradana (HAYATI Journal of Biosciences, 2023)
Leaf miners, Liriomyza spp., have developed as a severe pest in recent years, reducing the production of several ornamental and crops in Indonesia. As a result, monitoring and control mechanisms have been proposed. This research aimed to investigate community structure and identify Liriomyza spp., which impacts crops and natural parasitoids in Bali Province. Leaf samples of vegetables, ornamental plants, and related species were collected in all regencies/cities of Bali Province in 2019 and 2020 and preserved in the laboratory for observation and counting of leaf miners and related parasitoids. The findings revealed that four Liriomyza spp. were detected in host plants, namely Liriomyza sativae Blanchard (Diptera: Agromyzidae), Liriomyza huidobrensis Blanchard (Diptera: Agromyzidae), Liriomyza chinensis Kato (Diptera: Agromyzidae), and Liriomyza trifolii Burgess (Diptera: Agromyzidae). Asteraceae species were the most common host plants attacked by leaf miners in the field. The same occurrence was discovered at both heights (high and lowlands). The dry season is the most crucial component in the abundance of Liriomyza spp. In addition, parasitoids of the type Opius cromatomiyae Belokobylskij and Wharton (Hymenoptera: Braconidae) and Hemiptarsenun varicornis Girault (Hymenoptera: Eulophidae) were identified in abundance in Asteraceae plants. Similarly, the parasitization rate of the two parasitoids was found to be high in plants of the Asteraceae and Brassicae families. This approach highlights the decision-making process for controlling Liriomyza spp. on diverse host plant families by developing ecologically beneficial and sustainable parasitoids.